2023
DOI: 10.3389/fvets.2023.1205394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of florfenicol on nirS-type denitrifying communities structure of water in an aquatic microcosm model

Abstract: Florfenicol is used worldwide for its low side effects and strong bactericidal effect. Florfenicol is physicochemically stable and can persist in natural water bodies and affect water denitrification. Indoor aquatic microcosm models were constructed and water samples were collected at different florfenicol concentrations (0.1, 1, 10, and 100 mg/L) on days 0, 7, 30, and 60 to extract the microbial genome DNA and determine the water properties. qPCR and amplicon sequencing were used to study the dynamic changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(46 reference statements)
1
0
0
Order By: Relevance
“…Several studies have shown that florfenicol slightly promotes nitrite reductase encoding gene abundance for a short period of time [32,48]. The same phenomenon was found in our previous study: the florfenicol addition to aquatic microcosms suppressed the aquatic denitrifying microbial community diversity but increased the nirS gene abundance, and in addition, the treatment group with lower florfenicol addition induced a marked increase in florfenicol-resistant genes in aquatic environments [31,49]. This may be due to the combined effect of drug and time that some strains carrying nirS genes acquired florfenicol resistance genes and became dominant bacteria under florfenicol stress.…”
Section: Discussionsupporting
confidence: 86%
“…Several studies have shown that florfenicol slightly promotes nitrite reductase encoding gene abundance for a short period of time [32,48]. The same phenomenon was found in our previous study: the florfenicol addition to aquatic microcosms suppressed the aquatic denitrifying microbial community diversity but increased the nirS gene abundance, and in addition, the treatment group with lower florfenicol addition induced a marked increase in florfenicol-resistant genes in aquatic environments [31,49]. This may be due to the combined effect of drug and time that some strains carrying nirS genes acquired florfenicol resistance genes and became dominant bacteria under florfenicol stress.…”
Section: Discussionsupporting
confidence: 86%